DENTAL CALCULUS IN PRIMARY TEETH: AN INTEGRATIVE LITERATURE REVIEW - Caroline Ribeiro Lacerda, Anne; Helena de Brito Santos Lima, Edithe; Armentano de Amorim Leite, Giulia; Paulo Santos de Souza , Marcos; Gama de Oliveira Muniz , Letícia; Carvalho Rodrigues , Jamilly; Alves Freitas Cruz, Kádja; Siqueira Rodrigues, Matheus; Gabriel Gomes Rodrigues, Thalys; de Souza Pereira, Malvina (Health and Society, 2025)
Introduction: Dental calculus, also known as tartar, is the result of the mineralization of bacterial plaque that forms on the surface of the teeth. Its appearance in deciduous teeth causes concern and possible repercussions for the appearance and functionality of the dental arch. Objective: This integrative literature review aims to address the formation and impact of the presence of dental calculus in deciduous teeth. Methodology: The National Center for Biotechnology Information (NCBI), U.S. National Library of Medicine (PubMed) and Scientific Electronic Library Online (SciELO) databases were used. Articles published in the last 10 years, available in Portuguese, English and Spanish, were selected for their relevance, methodology and main findings. Discussion: Although the formation of dental calculus is more common in adults, it can also affect children during the deciduous and mixed dentition phases. Elucidating the need to introduce a balanced diet to avoid changes in the oral microbiota and increase in pathological dysbiosis. Furthermore, preventive habits are necessary to avoid the development of dental calculus in primary teeth. Conclusion: The presence of dental calculus in primary teeth represents an important risk factor for changes in children’s oral health. The adoption of preventive measures from childhood not only prevents damage to primary teeth, but also establishes solid foundations for oral health throughout life.